Anti-Inflammatory and Antioxidant Properties of Crude Methanol Extracts from the Flowers and Peels of Khlong Seng Local Durian (Durio Zibethinus Murr.) - Sang-Ngam, Surachai; Promden, Worrawat; Sangphech, Naunpun; Chukaew, Arnon; Sintupachee, Siriluk (Trends in Sciences, 2024)
The agricultural byproduct, represented by durian peels during the season, needs to be converted into economic value within the local area. This study aimed to assess the pharmaceutical properties, specifically antioxidant and anti-inflammatory effects, of methanol extracts from both flowers and peels of the local durian in the district. Additionally, in vitro testing was conducted to evaluate the impact on cells and the inhibition of nitric oxide induced by LPS. Results indicated that the flowers’ extract exhibited a higher concentration of antioxidants compared to the peels. The FRAP assay, using Trolox and Fe(II) as standards, showed statistically significant differences (p-value < 0.05) with values of 427.40 ± 7.64 µmole TE/g extract and 3,568.47 ± 77.55 µmole Fe(II) equivalent/g extract, along with a DPPH scavenging of 85.19 % and an IC50 of 114.50 ± 7.27 µg/mL. Concerning the inhibition of LPS-induced nitric oxide content, the peels’ extract, excluding KS7, demonstrated a response. KS10 exhibited the highest statistically significant difference (p-value < 0.05) in inhibition at concentrations of 0.6, 0.8 and 10 µg/mL, while others showed inhibition at 1.0 µg/mL. The outcomes of this research suggest the potential to enhance the value of agricultural waste, contributing to both the development of durian agriculture and public health at the local level. HIGHLIGHTS Exploring the antioxidant and anti-inflammatory attributes of Khlong Seng Local durian peel and flower The flowers primarily exhibit antioxidant properties, while the peel demonstrates anti-inflammatory characteristics across all samples of durians aged between 50 - 60 years The discovery highlighted the potential of agricultural waste, showcasing its capacity to be transformed into alternative products, thereby enhancing income opportunities for local farmers GRAPHICAL ABSTRACT